Acciones del estado ecuatoriano que garanticen el derecho a la educación ante la emergencia sanitaria - Sánchez Del Valle, Ana Daniela (2022)
The present study, entitled "Actions of the Ecuadorian State that guarantee the right to education in the event of a health emergency.", Which had as its main purpose to analyze the actions of the measures taken by the Ecuadorian State against the obligation to ensure the Right to Education in the face of the health emergency. In correspondence with the methodological route, the research is developed with a qualitative approach through the use of the hypothetical deductive method, which allowed the analysis through an interview. In this sense, the current regulations present sufficient regulation in order to protect the best interests of the Child and Adolescent, however, measures are not applied that guarantee the right to education in accordance and balance, so the activation of plans for permanent monitoring and control, since they do not effectively develop the right to educational training.